Recovery Rules: post-match recovery and load management during match congestion in elite team sport players - Doeven, S. (Universität Groningen, 2022)
Based on the findings in this thesis, trainers and coaches should be vigilant on hidden recovery processes. This can be the case if performance is already at baseline values while biochemical markers remain impaired by previous load. Adequate communication between coach and player adds to more insight in match exertion and the process of post-match recovery of the player. For optimal performance, discrepancy between coaches` and players` perceptions should be reduced to a minimum. Within intensified competition coaches tend to overcompensate training load. Match load indicators such as HIR and PC influence fatigue and general muscle soreness, respectively and might, therefore, be used as feedback parameters. Moreover, well-being, fatigue and TQR are most useful for their responsiveness to acute increased load.